2007
DOI: 10.1038/sj.bjc.6603952
|View full text |Cite
|
Sign up to set email alerts
|

PDK-1/AKT pathway as a novel therapeutic target in rhabdomyosarcoma cells using OSU-03012 compound

Abstract: Rhabdomyosarcoma (RMS) is the most common paediatric soft-tissue sarcoma including two major subtypes, alveolar rhabdomyosarcoma (ARMS) and embryonal rhabdomyosarcoma (ERMS). Increasing evidence suggests that oncogenesis of RMS involves multistages of signalling protein dysregulation which may include prolonged activation of serine/threonine kinases such as phosphoinositide-dependant kinase-1 (PDK-1) and AKT. To date, whether PDK-1/AKT pathway is activated in RMS is unknown. This study was to examine phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 17 publications
5
42
0
Order By: Relevance
“…Several other candidate genes have been linked to mTOR signaling (51), and positive p-S6 immunostaining confirmed enhanced mTOR signaling in Kras; p16p19 null sarcomas and in 26-33% of human RMS and leiomyosarcomas. Similarly, phosphorylation of AKT (another mTOR pathway component) was reported in 43-55% of human embryonal and alveolar RMS (52). Like Ras, pharmacological inhibition of mTOR signaling in mouse and human sarcoma cells impaired tumor growth, consistent with prior studies using RMS cell lines and xenografts (19,21) and with beneficial effects seen in some patients with advanced sarcomas (45).…”
Section: Discussionsupporting
confidence: 67%
“…Several other candidate genes have been linked to mTOR signaling (51), and positive p-S6 immunostaining confirmed enhanced mTOR signaling in Kras; p16p19 null sarcomas and in 26-33% of human RMS and leiomyosarcomas. Similarly, phosphorylation of AKT (another mTOR pathway component) was reported in 43-55% of human embryonal and alveolar RMS (52). Like Ras, pharmacological inhibition of mTOR signaling in mouse and human sarcoma cells impaired tumor growth, consistent with prior studies using RMS cell lines and xenografts (19,21) and with beneficial effects seen in some patients with advanced sarcomas (45).…”
Section: Discussionsupporting
confidence: 67%
“…Some researchers have found that OSU-03012 inhibited tumor cell viability, induced apoptosis in tumor cells, and did not induce detectable apoptosis in normal human cells. So, in the treatment of rhabdomyosarcoma, the novel OSU-03012 compound may be a more potent inhibitor of PDK-1/AKT pathway than the current potent inhibitor of PI3-K/AKT, LY294002 (Cen et al, 2007). In addition, the mammalian target of rapamycin (mTOR) inhibitors has been proven to have promising antitumor activity in patients with metastatic sarcoma (Vincezi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway is frequently activated in many cancers, 48 including ARMS. 38 This pathway is also activated and acts as a promyogenic signal following the exposure of normal myoblasts to differentiationpermissible conditions. 25,26 Because ARMS-T and ARMS-325 cells have an inactive terminal myogenic differentiation program (Fig.…”
Section: Conditional Mouse Models Of Arms Cells Are Defective In Termmentioning
confidence: 99%
“…Activation of AKT signaling pathway, which is a common lesion in many cancers, [35][36][37] is also found in ARMS. 38 Moreover, studies have found that AKT targets FKHR function in normal myogenic differentiation, 6,7 but its fusion derivative PAX3-FKHR abrogates such processes in ARMS. [18][19][20]23,39 However, the molecular mechanism(s) underlying activated AKT signaling in association with PAX3-FKHR in the suppression of myogenic differentiation program in ARMS remains unknown.…”
Section: Akt and Pax3-fkhr Cooperation Enforces Myogenic Differentiatmentioning
confidence: 99%